Comparison of efficiency for monoazo dye removal by different species of white-rot fungi - Pecková, V.; Legerská, B.; Chmelová, D.; Horník, M.; Ondrejovič, M. (International journal of environmental science and technology (Tehran), 2021)
The aim of this study was to determine the potential of white-rot fungi, namely Pycnoporus cinnabarinus , Pleurotus ostreatus and Trametes hirsuta , for the mono azo dye Allura Red AC (AR) removal from aqueous solutions. AR belongs to the hardly degradable xenobiotic associated with a neurotoxic effect on humans and animals. Our results suggested that degradation processes driven by the activity of laccases were not involved in the process of AR removal and the predominant mechanism of dye elimination was biosorption. The surface of fungal biomass was analyzed by Fourier transform infrared spectroscopy (FTIR) and Langmuir and Freundlich models of absorption isotherms were applied to describe the biosorption isotherms. Langmuir model fitted the equilibrium data better than Freundlich isotherm according to the corrected Akaike Information Criterion (AIC c ). From Langmuir model, dead biomass of P. ostreatus modified by heat was the most suitable biosorbent with the maximum sorption capacity of 118.3 ± 9.9 mg/g dried biomass. Obtained results suggest that biomass of white-rot fungi can be used as a suitable and low-cost biosorbent for the removal of azo dyes from contaminated waters.